The viability of an economic and monetary union in Africa with a unified currency: evidence from the African economies' reactions to the international income, price and monetary shocks - (:unkn) unknown (My University, 2013)
The purpose of this paper is to provide a framework to analyze the feasibility of an economic and monetary union in Africa with a common currency. In this context, the present study has two objectives. The first one is to analyze the impacts of the international income, price and monetary shocks on real GDP, household consumption and consumer prices index in 17 African countries using a SVAR model for the period 1970-2007. The research methodology adopted in this study suggests that 16 countries are exposed to the international income shock, nine to the international price shock and 10 to the international monetary shock. A decrease in real OECD GDP has a negative impact on real GDP, household consumption and consumer prices index, and inversely in the case of an increase. A decrease in current Federal funds effective rate has a positive effect on those variables, and inversely. World price of oil impacts essentially African oil producers, with a decrease affecting negatively their economies and an increase positively. The second one is to compare African economies' orthogonal impulse response functions to those international shocks. It can be observed that the functions tend to be similar in the cases of the real GDP and household consumption's reactions, and more or less similar in the case of the consumer prices index responses. This analysis emphasizes that the possibility of creating an economic union in Africa with a common currency does exist.
Keywords: African Research